CPEC and treatment accorded to Chinese investment in Pakistan under bilateral regime - HAMID MUKHTAR; KASHIF MAHMOOD SAQIB; ABDUL RASHEED; MUHAMMAD WAQAS JAVED (International Journal of Business and Economic Affairs, 2021)
Foreign Direct Investment (FDI) plays a significant role in the development and growth of the countries. In order to attract the foreign investors, States enter into bilateral investment treaties, focusing on the promotion and protection of investment. Pakistan and China are neighbors and enjoy long term economic and political relations. Friendship of China and Pakistan is termed as “all-weather-friendship”. Along-with a treaty of friendship and other significant treaties, China and Pakistan have also entered into three major bilateral treaties which specifically focus on the promotion of bilateral trade and investment and provide extended standards of protection for Chinese investment in Pakistan. Long standing relationship of China and Pakistan has been changed to geo-strategic and economic partnership which resulted into the agreements of mega projects under China-Pakistan Economic Corridor (CPEC). Under the said corridor, Chinese companies are investing billions of dollars in Pakistan. With the successful completion of CPEC, both the States will enjoy a lot of economic as well as strategic benefits. Research paper in hand explores CPEC and tries to enlist the treatment accorded to Chinese Investment in Pakistan under various national laws and bilateral agreements, so that Chinese Investor could be made aware of the legal issues involved in the way of foreign investment in Pakistan. Existing treaties between China and Pakistan and local laws of Pakistani that deal with foreign investment have been explored and analyzed for the above said purpose. Our research concludes that although Pakistan contains a quite liberal regime for Chinese investors in the Asian region.